Trends in Perinatal Mortality in Tribhuvan University Teaching Hospital: 13 Years Review - Shrestha, M; Shrestha, L; Basnet, S; Shrestha, PS (Journal of Nepal Paediatric Society, 2012)
Introduction: The perinatal mortality rate (PMR) in Nepal is still very high. In major hospitals of Nepal, it is still ranging from 20-30 per thousand births. This study was carried out with the objective to review PMR and classifying it according to Wigglesworth classification to identify the causes of perinatal deaths at Tribhuvan University Teaching Hospital (TUTH), Kathmandu, Nepal over the past 13 years and assess need for improvement in care. Material and Methods: It was a retrospective study carried out in TUTH. Data of all stillbirths from 28 weeks of pregnancy and neonatal deaths within first seven days of life in the hospital was taken from monthly perinatal audit and annual mortality review. All the perinatal deaths were then classified according to Wigglesworth classification. Results: Over a 13 year period, there were total 42,746 births and 921 perinatal deaths giving a perinatal mortality of 21.5 per thousand births. Over this period PMR has decreased from 31 to 18 per thousand births. Still births contributed almost 50% of the perinatal deaths; deaths related to prematurity show an increasing trend and have increased by almost 70% in past 5 years. Deaths due to perinatal asphyxia were static. Conclusion: PMR over the years has shown declining trend at TUTH. There is need to improve antenatal, obstetric as well as intrapartum services to further reduce the still birth as well as deaths due to prematurity and perinatal asphyxia. J. Nepal Paediatr. Soc. 32(2) 2012 150-153 doi: http://dx.doi.org/10.3126/jnps.v32i2.6898